Penggunaan Alat Peraga Edukatif "Magic Box" Dalam Pembelajaran Matematika Untuk Meningkatkan Hasil Belajar Siswa Kelas V SD Muhammadiyah 16 Surakarta Tahun Pelajaran 2016/ 2017 - Ismiyasari, Fatimah Nur; , Drs. H. Mulyadi Sri Kamulyan, S.H, M.Pd (2017)
The study aims to: (1) describe the use of the magic box educative aids for Mathematics learning of the 5th grade students of SD Muhammadiyah 16 Surakarta in 2016/ 2017, (2) identify the problem faced in the implementation the magic box educative for mathematics learning of the 5th grade students of SD Muhammadiyah 16 Surakarta in 2016/ 2017, dan (3) to increase the learning outcome for mathematics in the implementation the magic box educative for mathematics learning of the 5th grade students of SD Muhammadiyah 16 Surakarta in 2016/ 2017. It was a collaborative class action research. The techniques of the data gathering comprised observation, interview, test, and documentation. The results show that 1) there was an increased Mathematics learning outcome, i.e., from 30.77% into 94.87%. It indicates that the students could achieve KKM ≥75; the students in an average of 66.95 into 82.67 amounted to 35 people, so that the indicator of learning outcome at 75% could be achieved. 2) Constraints encountered in the use of the magic box educative aids for Mathematics learning of the 5th grade students of SD Muhammadiyah 16 Surakarta in 2016/ 2017 is student tend to be passive and less confident, less teachers skilled in the use of the magic box educative, conditioning of students in class . 3) There was an increased learning activity, i.e., the lowest score of 1 into 9 and the highest score of 4 into 15. The inactive students into the very active ones in learning activity achieved ≥75% of the previously active students.